Role of Dietary Nitrate for Human Health: A Narrative Review - Ferdina, Ayunina Rizky; Setiawan, Muhammad Irwan (Iraqi Journal of Pharmaceutical Sciences, 2024)
There has been a perspective shift regarding the role of inorganic nitrate consumption in human health. It was once thought to be a potentially harmful food additive, but more research has been conducted on the potential health benefits of dietary nitrate. This narrative review aimed to summarize important findings about the role of dietary nitrate in human health. Literature search was performed through PubMed and Google Scholar on the topics of dietary inorganic nitrate. This brief review was then synthesized summarizing the current evidence concerning its dietary source, safety concern, metabolism, and some potential health benefits. There is no compelling evidence to support the concerns about the toxic effects of nitrate as a food preservative. Instead, it has been discovered that vegetables are the primary source of inorganic nitrate, which may provide a variety of health benefits via the nitrate-nitrite-nitric oxide pathway. Although the research is still in its early stages, nitrate and its derivatives have the potential to act as antibiofilm agents. Dietary nitrate can improve cardiovascular health as a result of its conversion to nitric oxide. Dietary nitrate has also been recommended as a sports supplement because it has been shown to improve athletic performance. Nitrate consumption may also be beneficial in the treatment of several other medical conditions, including Covid-19. Dietary nitrate can boost production of nitric oxide which is beneficial for health. All current findings regarding the benefits of naturally occurring nitrate substantiate the recommendation of daily vegetable consumption.